44.9k views
4 votes
Jade wants to verify that the expression 5(3x – 6) is equivalent to 15x – 30. She substitutes 2 into each expression and evaluates each one. How will she know if 5(3x – 6) is equivalent to 15x – 30?

2 Answers

3 votes

Answer:

See below.

Explanation:

If the evaluations are the same she will know they are equivalent.

First try 5(3x - 6):

5(3(2) - 6) = 5 * (6 - 6)

= 5 * 0

= 0.

Now try 15x - 30:

15(2) - 30

= 30 - 30

= 0.

So they are equivalent.

User Sajan Chandran
by
5.0k points
3 votes

Answer:

expand the brackets of 5(3x-6)

so 15x - 30

substituting 2 into both expressions will give you 0. therefore they are equivalent.

User David Goss
by
5.6k points